ANALISIS PENGARUH ALIRAN SUPPLY CHAIN MATERIAL DAN ALAT BERAT TERHADAP KINERJA PROYEK PEMBANGUNAN JALAN TOL - Deby Lelita Maryuni; I Nyoman Dita Pahang Putra (LPPM Universitas Abdurrab, 2025)
The construction industry plays a vital role in the national economy, especially in toll road projects that require speed, high quality, and cost efficiency. Project success largely depends on the smooth flow of material and heavy equipment supply chains, as delays can lead to project setbacks and increased costs. This research aims to analyze the impact of the material and heavy equipment supply chain flow on the performance of the Solo-Yogyakarta-NYIA Kulon Progo Toll Road Project Section II Package 2.2B and to identify the influencing factors. The research methodology employed a quantitative approach with questionnaire distribution to project employees, utilizing the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results of the T-test analysis indicate that the material and heavy equipment supply chain flow has a positive and significant effect on project performance by 60.6%. Based on the multiple linear regression test results, the equation Y = 1.438 + 2.615X1 + 0.423X2 was obtained, demonstrating that all variables of the material (X1) and heavy equipment (X2) supply chain influence the performance of the toll road project. The most influential factors on the material and heavy equipment supply chain flow affecting project performance are communication constraints during the project and the operational methods of heavy equipment. This research is expected to provide new insights for construction practitioners in optimizing supply chain management, enhancing the efficiency and effectiveness of toll road construction projects.